Better tests, better care: improved diagnostics for infectious diseases - Caliendo, Angela M; Gilbert, David N; Ginocchio, Christine C; Hanson, Kimberly E; May, Larissa; Quinn, Thomas C; Tenover, Fred C; Alland, David; Blaschke, Anne J; Bonomo, Robert A; Carroll, Karen C; Ferraro, Mary Jane; et al. (Clinical infectious diseases, 2013)
In this IDSA policy paper, we review the current diagnostic landscape, including unmet needs and emerging technologies, and assess the challenges to the development and clinical integration of improved tests. To fulfill the promise of emerging diagnostics, IDSA presents recommendations that address a host of identified barriers. Achieving these goals will require the engagement and coordination of a number of stakeholders, including Congress, funding and regulatory bodies, public health agencies, the diagnostics industry, healthcare systems, professional societies, and individual clinicians.